2x+2(-3x+2)=48

Simple and best practice solution for 2x+2(-3x+2)=48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+2(-3x+2)=48 equation:


Simplifying
2x + 2(-3x + 2) = 48

Reorder the terms:
2x + 2(2 + -3x) = 48
2x + (2 * 2 + -3x * 2) = 48
2x + (4 + -6x) = 48

Reorder the terms:
4 + 2x + -6x = 48

Combine like terms: 2x + -6x = -4x
4 + -4x = 48

Solving
4 + -4x = 48

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -4x = 48 + -4

Combine like terms: 4 + -4 = 0
0 + -4x = 48 + -4
-4x = 48 + -4

Combine like terms: 48 + -4 = 44
-4x = 44

Divide each side by '-4'.
x = -11

Simplifying
x = -11

See similar equations:

| 7x^2=-8 | | -4.5x+12.3=-23 | | H/4=3.1 | | -5x+3=x-12 | | 2/3(x+1)=4/9x+14/9 | | x-10+3x-6= | | -2d=-d+10 | | xy(xy-u)= | | .75x+4.50=1.25x+2.50 | | 4k=3.6 | | 1/25:3=x:12 | | sinx=0.927 | | 3k=8+4k | | 2w=3w+10 | | -6=x-14+7x | | .5(6x+10)=20 | | q+70=55 | | -35-x=31+5x | | 3t+3=6t+9 | | (5x^2+1)(6x^2+4)=1 | | G/3=3.9 | | 3(x-5)-4(2x-3)=7 | | (2y+3y)2= | | x-.85x=32.89 | | 6a-10+5a=6a+20 | | 5+1.5(2m-1)=0.5 | | 5n+35+50=160 | | 58=1/2-x | | Sqrt(-7-7x)+3=10 | | 2/5x+1/10=1/2(x+4) | | 6a-10a+5a=6a+20 | | 58=1/2x |

Equations solver categories